Gastropods In Mangrove Forest Of Tongkeina Village, Bunaken Sub-District, City Of Manado - Dewanti Y Talumingan; Ferdinand F. Tilaar; Jety K. Rangan; Maartinus Baroleh; Victor N. R. Watung; Agung B. Windarto (Sam Ratulangi University, 2021)
This research aims to determine the types or species of gastropod and its distribution in mangrove forests in Tongkeina village and to know the species of mangrove in Tongkeina village. The Research was conducted on one sampling point with one 100 meters long line transect which was is laid perpendicular to the outer direction of the mangrove.Â To collect gastropod samples, three quadrates with a size of 10x10meters with a distance between the quadrate 5 meters were made. In the quadrate, 15 subquadrates sized 1x1meters were also made. Based on the results, there were 6 species of gastropods and two distribution patterns of i.e., Cluster the species of the Littoraria scabra, Angustassiminea castanea, Terebralia sulcate. The uniform distribution pattern is Ischinocerithium rostratum, Caliostoma jujubinum, and Nerita senegalensis. There are ten mangrove species found andÂ the most common species is Soneratia alba with a total of 27 individuals.Keywords: Gastropods, forest, Mangrove, Tongkeina villageÂ ABSTRAKPenelitian ini bertujuan untuk mengetahui Jenis-jenis gastropoda serta persebaran pada hutan mangrove di Kelurahan Tongkeina dan untuk mengetahui Jenis-jenis mangrove di Kelurahan Tongkeina. Penelitian hanya di lakukan satu titik pengambilan sampel dimana dibuat 1 line transek dengan Panjang 100meter yang di tarik tegak lurus dari arah terluar mangrove kemudian dibuat 3 kuadrat dengan ukuran 10x10meter dengan jarak antara kuadrat 5 meter, dan di dalam kuadrat dibuat 15 subkuadrat berukuran 1x1 meter. Berdasarkan penelitian hasil ditemukan ada 6 spesies gastopoda dan dua pola persebaran Gastropoda yaitu mengelompok dan seragam, spesies mengelompok yaitu Littoraria scabra, Angustassiminea castanea, Terebralia sulcate. Pola persebaran seragam yaitu Ischinocerithium rostratum, Caliostoma jujubinum, Nerita senegalensis. Mangrove ditemukan 10 Spesies yang terbanyak adalah Soneratia alba dengan jumlah 27 individu.Kata kunci: Gastropoda, Hutan, Mangrove, Kelurahan Tongkeina.